Multi‐Level Approach for Comprehensive Enamel Phenotyping. Issue 1 (10th January 2022) - Aranaz‐Novaliches, Goretti; Spoutil, Frantisek; Bukova, Ivana; Krejzova, Irena; Olsinova, Marie; Dalecka, Marketa; Benda, Ales; Rozman, Jan; Sedlacek, Radislav; Prochazka, Jan
Abstract: Enamel is the hardest tissue in mammalian organisms and is the layer covering the tooth. It consists of hydroxyapatite (HAP) crystallites, which mineralize on a protein scaffold known as the enamel matrix. Enamel matrix assembly is a very complex process mediated by enamel matrix proteins (EMPs). Altered HAP deposition or disintegration of the protein scaffold can cause enamel defects. Various methods have been established for enamel phenotyping, including MicroCT scanning with various resolutions from 9 µm for in vivo imaging to 1.5 µm for ex vivo imaging. With increasing resolution, we can see not only the enamel layer itself but also a detailed map of mineralization. To study enamel microstructure, we combine the MicroCT analysis with scanning electron microscopy (SEM), which enables us to perform element analyses such as calcium‐carbon ratio. However, the methods mentioned above only show the result—already formed enamel. Stimulated emission depletion (STED) microscopy provides extra information about protein structure in the form of EMP localization and position before enamel mineralization. A combination of all these methods allows analyzing the same sample on multiple levels—starting with the live animal being scanned harmlessly and quickly, followed by sacrifice and high‐resolution MicroCT scans requiring no special sample preparation. The biggest advantage is that samples remain in perfect condition for SEM or STED microscopic analysis. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : In vivo MicroCT scanning of mouse Basic Protocol 2 : Ex vivo HR‐MicroCT of the teeth Basic Protocol 3 : SEM for teeth microstructure Basic Protocol 4 : Stimulated emission depletion (STED) microscopy